2020
DOI: 10.3389/fmicb.2020.00199
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Rain as Source of Biological Control Agents for Fire Blight on Apple

Abstract: Poor survival on plants can limit the efficacy of Biological Control Agents (BCAs) in the field. Yet bacteria survive in the atmosphere, despite their exposure to high solar radiation and extreme temperatures. If conditions in the atmosphere are similar to, or more extreme than, the environmental conditions on the plant surface, then precipitation may serve as a reservoir of robust BCAs. To test this hypothesis, two hundred and fifty-four rain-borne isolates were screened for in vitro inhibition of Erwinia amy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…Antagonistic bacteria such as Pseudomonas, Pantoea, Enterobacter, Serratia, and Bacillus genera were reported for control of fire blight to suppress E. amylovora. For example, Pantoea agglomerans, B. subtilis, Bacillus amyloliquefaciens, and Pseudomonas fluorescens were registered bacteria products and commercially available (Dagher et al, 2020;Mechan Llontop et al, 2020;Mikiciński et al, 2016;Sharifazizi et al, 2017). Recently, use of phage therapy as biological control has been emphasized, in which bacteriophages are expected to prevent bacterial infections.…”
mentioning
confidence: 99%
“…Antagonistic bacteria such as Pseudomonas, Pantoea, Enterobacter, Serratia, and Bacillus genera were reported for control of fire blight to suppress E. amylovora. For example, Pantoea agglomerans, B. subtilis, Bacillus amyloliquefaciens, and Pseudomonas fluorescens were registered bacteria products and commercially available (Dagher et al, 2020;Mechan Llontop et al, 2020;Mikiciński et al, 2016;Sharifazizi et al, 2017). Recently, use of phage therapy as biological control has been emphasized, in which bacteriophages are expected to prevent bacterial infections.…”
mentioning
confidence: 99%
“…agglomerans isolate against E . amylovora (Mechan Llontop et al, 2020). Our data are also consistent with the literature and the emerging view of the antimicrobial activity of AGA against the phytopathogen E .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, AGA itself is toxic to P. agglomerans Eh1087, and the phz pathway encodes a special phenazine-binding protein, EhpR, that prevents self-poisoning of the producer (Giddens et al, 2003;Mavrodi et al, 2010). Very recently, Mechan et al ( 2020) also have pointed to, using a UV-mutagenesis screen, the AGA synthesis gene cluster as being at the base of the antimicrobial activity of the P. agglomerans isolate against E. amylovora (Mechan Llontop et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Higher humidity due to these treatments might have enhanced growth of these bacteria. In agriculture, it has often been reported that high humidity or precipitation enhance activities of pathogenic Erwinia and Pseudomonas, and increase damage by diseases [49][50][51].…”
Section: Identification Of Bacteria That Were Increased By Inoculationmentioning
confidence: 99%
“…Besides, we found significant negative associations between the proportion of the ASVs of Cluster 5 and fruit set based on the GLMM analysis, while we did not for seed set. Since Erwinia and Pseudomonas include plant pathogens that trigger abortion of flowers and fruits [51][52][53], some of these bacteria might have negatively affected fruit development by infecting a reproductive organ. However, we cannot rule out other potential explanations about the correlation.…”
Section: Effects Of Old-flower Microbes On Fruit and Seed Productionmentioning
confidence: 99%